Estudo de utilização de comprimidos partidos em ambiente hospitalar: análise de prescrições e avaliação laboratorial da qualidade de comprimidos partidos - Melo, Vivianne Vieira de (2018)
Introduction: The practice of tablet splitting has been widely performed and motivated for several reasons, however, partitioning may be associated with imprecision of the administered dose and loss of drug stability. Considering the potential of tablet splitting to change the effectiveness and safety of drug therapy it becomes essential to know the frequency of tablet splitting and to determine the quality of this splitting in order to provide technical recommendations on this important practice. Purpose: To analyze the using profile of tablets splitting in a hospital and to investigate their quality by laboratory tests. Methods: The frequency of tablet splitting was verified in prescriptions of Pharmacy Sector of a university hospital. Prescriptions for thirteen random days were collected between January and March 2016. The fourteen tablets most frequently prescribed to be splitting were split using commercial tablet cutter. Loss and mass variation tests, as well as the evaluation of the friability of the split halves were performed. Results: 238 tablets were splitted in the study (4.5% of total tablets prescribed), with clonazepam (25.2%) being the most frequently used, followed by warfarin (11.3%) and propranolol (7, 1%). About three quarters of the tablets were splitted by medical decision. More than 95% of the tablets were splitted in a half and to 85.1% a pharmaceutical alternative was available in Brazilian market. The laboratory tests showed loss mass mean and mean mass variation of 8.7% ± 1.8% and 11.7% ± 2.3%, respectively. The friability after the tablets splitting increased by an average of 3.3%. Discussion: The mean tablet splitting frequency was lower than those described in other studies. However, the existence of pharmaceutical alternatives in Brazilian market for most of the tablets splitting suggested that the process of standardizing medications in the hospital, as well as the knowledgment about tablet split by pharmacists and physicians needs to be improved to rationalize the tablet splitting practice in the hospital environment. In the present study, a strong association was observed between the tablet splitting and the age group, which is more frequent in elderly patients. Laboratory tests showed mean values of loss mass and mass variation similar to those described in the literature. The presence of score had positively influenced the obtaining of more homogeneous halves, and the presence of the coating gave a reduction of the mass loss. Conclusion: The set of findings reported here allowed us to observe that the tablets splitting in the hospital has been done in part unnecessarily and laboratory tests have shown that there is a potential health risk due to a reduction in the quality of the broken tablets.